Can command-and-control policy drive low-carbon transition in energy-intensive enterprises? -a study based on evolutionary game theory - Zhou, Chunxi; Han, Yang; Zhang, Ruiqi (Frontiers in Energy Research, 2023)
There are two views on whether command-and-control policy can promote carbon emission reduction: the “compliance cost” theory and the “innovation compensation” theory. In this paper, we construct an evolutionary game model among energy-intensive enterprises, verification agencies, and local governments from the game theory perspective to explore the impact of command-and-control policy on the low-carbon transition of energy-intensive enterprises. The interaction mechanism of the three actors and the main factors affecting the low-carbon transition of the enterprises are further analyzed with the help of the MATLAB simulation method. The study results show that command-and-control policies can promote the low-carbon transition of enterprises and have a suppressive effect on bribery behavior. In the actual game process, enterprises will compare the cost of low-carbon transition with that of no low-carbon transition. The cost of low-carbon transition is higher when the government’s incentives and penalties are small, so there is a “compliance cost” effect, and the government cannot promote low-carbon transition by increasing the intensity of regulation. On the contrary, when the government’s incentives and penalties are strong enough, enterprises will make a low-carbon transition spontaneously in the face of continuously increasing environmental regulation intensity, which supports the theory of “innovation compensation.” In addition, increasing the profitability of product sales and increasing the cost of bribes are also effective ways to promote low-carbon transition. Finally, relevant policy recommendations were proposed based on the main conclusions. This work opens up a new perspective for environmental regulation theory and provides a theoretical reference and practical basis for developing low-carbon transition.